Patient-Reported and Oncological Outcomes of Salvage Therapies for PSMA-Positive Nodal Recurrent Prostate Cancer: Real-Life Experiences and Implications for Future Trial Design - Kretschmer, Alexander; Milow, Johanna; Eze, Chukwuka; Buchner, Alexander; Li, Minglun; Westhofen, Thilo; Fuchs, Frederik; Rogowski, Paul; Trapp, Christian; Ganswindt, Ute; Zacherl, Mathias Johannes; Beyer, Leonie; et al. (Frontiers in Oncology, 2021)
Introduction: The role of salvage lymph node dissection (SLND) and radiotherapy (SLNRT) in the management of nodal-only recurrent prostate cancer (PC) remains controversial. In addition, impact on health-related quality of life (HRQOL) has not been adequately evaluated yet. Materials and Methods: Analysis was limited to patients that were diagnosed with nodal-only recurrent PC via PSMA-PET/CT. SLND was performed via open approach. For SLNRT, dose regimens were normo- or slightly hypo-fractionated with a simultaneous boost to the PET-positive recurrences. EORTC QLQ-C30 and PR-25 questionnaires were used to assess HRQOL. Continence status was assessed using daily pad usage and the validated ICIQ-SF questionnaire. For multivariable analysis, Cox regression models were used (p<0.05). Results: 138 patients (SLND: 71; SLNRT: 67) were included in the retrospective analysis. Median follow-up was 47 months (mo) for SLNRT patients (IQR 40–61), and 33mo for SLND patients (IQR 20–49; p<0.001). In total, 61 patients (91.0%) in the SLNRT cohort and 43 patients (65.2%; p<0.001) in the SLND cohort underwent ADT anytime during the follow-up period. In multivariate Cox regression analysis, SLNRT could be confirmed as an independent predictor for increased PSA progression-free survival (PFS; HR 0.08, 95%CI 0.040 – 0.142, p<0.001). Estimated median metastasis-free survival (MFS) was 70mo for the total cohort without statistically significant differences between both subgroups (p=0.216). There were no significant differences regarding general HRQOL, daily pad usage, and ICIQ-SF scores between the respective cohorts. Conclusions: In a large contemporary series of patients with nodal-only recurrent PC based on PSMA-PET/CT staging, we observed significantly increased PSA PFS in patients undergoing SLNRT while no significant differences could be observed in MFS, and functional outcomes including HRQOL.